Research progress on common sports injuries among youth ice hockey players and prevention strategies: a narrative review - Zheng, Y.; Liu, Y.; Chen, Y.; Cao, J.; Chen, E.; Pan, H.; Huang, P. (Sports, 2025)
Background: Ice hockey is a high-intensity collision sport with one of the highest injury rates among youth team sports. Despite advanced protective equipment, youth athletes remain particularly vulnerable due to their unique physiological and psychological characteristics.